Comparison between cardiac resynchronization therapy with and without defibrillator on long-term mortality: A propensity score matched analysis. Issue 4 (April 2020) - Liang, Yixiu; Wang, Jingfeng; Yu, Ziqing; Zhang, Mingliang; Pan, Lei; Nie, Yuxin; Su, Yangang; Ge, Junbo
Highlights: A total of 345 patients were recruited and followed up for a median time of 36 months. CRT-D did not significantly reduce mortality compared with CRT-P in primary analysis. Propensity score matched analysis showed no difference in mortality between CRT-D and CRT-P. No single baseline factor distinguishes the effect of CRT-D and CRT-P on mortality. Abstract: Background: Cardiac resynchronization therapy (CRT)-defibrillator (CRT-D) has been more widely implanted than CRT-pacemaker (CRT-P) in patients of heart failure with reduced ejection fraction and prolonged QRS duration. However, the superiority of CRT-D over CRT-P in improving prognosis has not been well established. Methods: Consecutive patients who underwent CRT implantation between 2005 and 2016 were retrospectively recruited and followed up to December 2017. Baseline characteristics were collected and all-cause mortality was compared between CRT-D and CRT-P recipients. Propensity score matched analysis was further performed to validate the results. Results: A total of 345 patients (219 CRT-D, 126 CRT-P) were included. During a median follow-up of 36 months, there were 81 deaths (37.0%) in the CRT-D group compared to 56 deaths (44.4%) in the CRT-P group. There was no significant difference in the risk of mortality between CRT-D and CRT-P groups [hazard ratio (HR) 0.99, 95% CI 0.70–1.40, p  = 0.95]. Propensity score matching yielded 111 cases per group, and there was no significant difference in the risk of mortality between CRT-D and CRT-P groups (HR 0.87, 95%CI 0.57–1.34, p  = 0.53). No significant difference between CRT-D and CRT-P in reducing mortality was observed in any pre-specified subgroups, although the difference between CRT-D and CRT-P was more pronounced in patients with left bundle branch block ( p  = 0.01 for interaction). Conclusions: CRT-D did not reduce all-cause mortality compared with CRT-P in this retrospective propensity score matched study. A comprehensive score system incorporating multiple factors is needed for risk stratification and guidance on device selection.